Cost‐Effectiveness of Intensifying Lipid‐Lowering Therapy With Statins Based on Individual Absolute Benefit in Coronary Artery Disease Patients. Issue 2 (18th February 2017) - Stam‐Slob, Manon C.; van der Graaf, Yolanda; Greving, Jacoba P.; Dorresteijn, Jannick A.N.; Visseren, Frank L.J.
Abstract : Background: A validated prediction model estimates the absolute benefit of intensive versus standard lipid‐lowering therapy (LLT) with statins on next major cardiovascular events for individual patients with coronary artery disease. We aimed to assess whether targeting intensive LLT therapy to coronary artery disease patients with the highest predicted absolute benefit is cost‐effective compared to treating all with standard or all with intensive LLT. Methods and Results: A lifetime Markov model was constructed for coronary artery disease patients (n=10 000) with mean age 61 years. Number of major cardiovascular events, (non) vascular death, costs, and quality‐adjusted life years (QALYs) were estimated for the following strategies: (1) standard LLT for all (reference strategy); (2) intensive LLT for those with 5‐year absolute major cardiovascular events risk reduction (ARR) ≥3%, ≥2.3%, or ≥1.5% (corresponding to ≥20%, ≥15%, or ≥10% 5‐year major cardiovascular events risk); and (3) intensive LLT for all. With intensive LLT for those with ≥3% 5‐year ARR (13% of patients), 380 QALYs were gained for €2423/QALY. Using a threshold of ≥2.3% ARR (26% of patients), 630 QALYs were gained for €5653/QALY. Using a threshold of ≥1.5% ARR (56% of patients), 1020 QALYs were gained for €10 960/QALY. By treating all intensively, 1410 QALYs were gained (0.14 QALY per patient) for €17 223/QALY. With benefit‐based treatment, 0.16 to 0.17 QALY was gained per treated patient. Conclusions: Intensive LLT with statins for all coronary artery disease patients results in the highest overall QALY gain against acceptable costs. However, the number of QALYs gained with intensive LLT by statins in individual patients can be increased with selective benefit‐based treatment. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT00327691 and NCT00159835